Perancangan Digital Logbook Pada Shared Service Center PT. Pertamina Dengan Pendekatan Persuasive Design - Kusumadya, M. Agil; Amin, Zaid; Huda, Nurul; Suyanto, S (LPPM STIKOM Tunas Bangsa, 2024)
In this study, the researchers developed a Digital Logbook application using PHP with a MySQL database to capture operational data at SSC ICT PT Pertamina (Persero) Refinery Unit III Plaju. This application is expected to enhance the company's ability to achieve its goals and mission more effectively. The digital logbook, also known as an electronic notebook, is based on software that collects, stores, and organizes key data in a digital format. It is used to capture and store various types of information, such as operational records, incident reports, and current activities, as well as to document monthly reports.The methodology employed in the development of this website integrates Persuasive Design with a qualitative approach, starting with the formulation of needs analysis and using the Waterfall method to develop the system prototype. This approach ensures that employees at SSC ICT PT Pertamina (Persero) Refinery Unit III Plaju have a clear understanding of the system being developed. Additionally, it encourages staff to consistently use the system once it has been completed and tested. Persuasive Design is a practical design discipline focused on influencing human behavior through the characteristics of a product or service.